MODEL EXPLICIT INSTRUCTION DALAM MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR IPA KELAS III SDN 09 MATTEKKO KECAMATAN BARA KOTA PALOPO - Nurhatika Nurhatika (Journal of Teaching dan Learning Research, 2019)
This study aims to improve the activities and learning outcomes of Class III Science through the application of the Explicit Instruction model to Grade III students of SDN 09 Mattekko, Bara Subdistrict, Palopo City. This research is a classroom action research (PTK) and those who acted as research subjects were 26 students. Data collection techniques are carried out through observation, documentation and tests. Data analysis conducted in this study is descriptive analysis, namely data reduction, data presentation and conclusion drawing. The results showed that: 1) By applying the Explicit Instruction model was able to increase the activity and learning outcomes of Class III Science in SDN 09 Mattekko, Bara District, Palopo City. 2) Using the Explicit Instruction model in science learning is done in stages, namely three cycles experiencing a significant increase in which the learning activities of students in the first cycle are categorized as "sufficient" from the percentage value of 66.66% with the average value of the results. learning by 63, in the second cycle observation of student learning activities categorized as "Good" from the percentage value of an average of 77.15% with an average value of learning outcomes of 77.08, and in the third cycle observation of student learning activities is categorized as "Good" from the percentage value of an average of 87.25% with an average value of learning outcomes of 82.8. Thus, the Explicit Instruction model needs to be used as a reference by the teacher in learning to improve the activities and learning outcomes of science in elementary schools, especially SDN 09 Mattekko, Bara District, Palopo City.